Controlling the Anchoring Effect through Transcranial Direct Current Stimulation (tDCS) to the Right Dorsolateral Prefrontal Cortex - Li, Jianbiao; Yin, Xile; Li, Dahui; Liu, Xiaoli; Wang, Guangrong; Qu, Liang (Frontiers in Psychology, 2017)
Selective accessibility mechanisms indicate that anchoring effects are results of selective retrieval of working memory. Neuroimaging studies have revealed that the right dorsolateral prefrontal cortex (DLPFC) is closely related to memory retrieval and performance. However, no research has investigated the effect of changing the cortical excitability in right DLPFC on anchoring effects. Transcranial direct current stimulation (tDCS) can modulate the excitability of the human cerebral cortex, while anodal and cathodal tDCS are postulated to increase or decrease cortical activity, respectively. In this study, we used tDCS to investigate whether effects of increased or decreased right DLPFC excitability influence anchoring effects in willingness to pay (WTP) experiments. Ninety participants were first randomly assigned to receive either anodal, cathodal, or sham stimulation of 15 minutes, then they performed a valuation task regarding WTP. The results showed that anchoring effects were negatively related to activities of right DLPFC: the anodal stimulation diminished anchoring effects while the cathodal stimulation increased anchoring effects. These outcomes provide one of the first instances of neural evidence for the role of the right DLPFC in anchoring effects and support psychological explanations of the selective accessibility mechanisms and cognitive sets.